2022
DOI: 10.3390/su142013018
|View full text |Cite
|
Sign up to set email alerts
|

Green Defense Industries in the European Union: The Case of the Battle Dress Uniform for Circular Economy

Abstract: As climate change is at the top of the world’s agenda, the armed forces and other defense actors must give a signal that they are environmentally responsible. In this regard, the defense industry should be one of the first actors to devise new strategies and actions aimed at reducing the environmental footprint. This article focuses on the measures being taken by the defense industry and the armed forces, and on how technology, the circular economy (CE) and Lean principles can contribute to a better environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…They also identified the link between militarization, energy use, and environmental damage from the fuel consumption of military elements. In line with our arguments in this present study, Reis et al [37] adopted a different method, touching on the relationship between militarization and carbon footprint. Based on systematic literature review and case study researches, the authors find that European Union defense industry plays a crucial role on circular economy.…”
Section: Relevant Literaturesupporting
confidence: 80%
“…They also identified the link between militarization, energy use, and environmental damage from the fuel consumption of military elements. In line with our arguments in this present study, Reis et al [37] adopted a different method, touching on the relationship between militarization and carbon footprint. Based on systematic literature review and case study researches, the authors find that European Union defense industry plays a crucial role on circular economy.…”
Section: Relevant Literaturesupporting
confidence: 80%
“…A prime example of this is Old Navy's revamp of its marketing approach to cater to the younger generation. As noted by Reis et al (2022), Old Navy adjusted its strategy to attract millennials by employing digital marketing campaigns and partnering with social media influencers. This case study underscores the significance of aligning marketing strategies with the target audience's preferences and behaviors, leading to a notable rise in engagement and sales (Reis et al, 2022).…”
Section: Results Of the Study Case Study: Successful Integration Exam...mentioning
confidence: 99%
“…In addition, the analysis of the latest sources [41][42][43][44][45][46][47][48][49] also showed that the greatest attention is paid to the circular economy and civilian logistics, as well as aspects of reverse logistics in it, while such a significant aspect as the interaction of circular and reverse logistics in the military sector is almost not examined. Therefore, this gap allows us to assume and inspire further discussion at the level of scientific research.…”
Section: Disposalmentioning
confidence: 99%